2017
DOI: 10.1002/adfm.201604624
|View full text |Cite
|
Sign up to set email alerts
|

Significant Enhancement of Proton Transport in Bioinspired Peptide Fibrils by Single Acidic or Basic Amino Acid Mutation

Abstract: Bioinspired materials are extremely suitable for the development of biocompatible and environmentally friendly functional materials. Peptide‐based assemblies are remarkably attractive for such tasks, since they provide a simple way to fuse together functional and structural protein motifs in artificial materials. Motivated by this idea, it is shown here that the introduction of a single acidic, or basic, amino acid into the side chain of a heptameric self‐assembling peptide increases proton conduction in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 69 publications
(94 reference statements)
1
52
0
Order By: Relevance
“…It was further observed by applying both AC and DC bias and changing the relative humidity, that the thiophene‐containing peptide fibrils exhibited both electron and proton conductivity . In a similar type of conduction measurements, it was also observed that substituting the Lys residue with Glu resulted in more than an order of magnitude increase in conductance across the fibrils networks, while the Gln substitution resulted in a significant decrease in conductance (Figure b) …”
Section: Biomolecular Electronic Materials At the Macroscalementioning
confidence: 67%
See 2 more Smart Citations
“…It was further observed by applying both AC and DC bias and changing the relative humidity, that the thiophene‐containing peptide fibrils exhibited both electron and proton conductivity . In a similar type of conduction measurements, it was also observed that substituting the Lys residue with Glu resulted in more than an order of magnitude increase in conductance across the fibrils networks, while the Gln substitution resulted in a significant decrease in conductance (Figure b) …”
Section: Biomolecular Electronic Materials At the Macroscalementioning
confidence: 67%
“…Short peptides with the sequence of the core recognition motif (or similar sequences) can both inhibit the fibrillization process, as well as forming similar amyloid‐like structures by themselves . In recent years, Ashkenasy and co‐workers have used these short peptides as well as other fibril‐forming short peptides to increase the conduction across amyloid‐like fibrils . The main advantage of using short peptide sequences is the relative ease of chemical modifications in terms of amino acids and sequence changes.…”
Section: Biomolecular Electronic Materials At the Macroscalementioning
confidence: 99%
See 1 more Smart Citation
“…[24,25] The third direction is a new generation of bioinspired self-assembled synthetic peptide nanomaterials, [26][27][28] their nanotechnology, [29,30] physics, and engineering. [31][32][33][34] These materials of biological origin already showed potential applications in a variety of new fields, [35] such as piezoelectric energy harvesting devices and sensors, [36,37] displays and light-emitting devices, [38] superhydrophobic surfaces for self-cleaning, [29] composite reinforcement scaffolds, [39] flexible biodegradable electronics, [34] and more.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that proteins and β-sheet assemblies have shown to be excellent proton conductors. [34][35][36][37] Due to the presence of rich hydrogen bonding, proton accepting and proton donating groups, proteins and the β-sheet fibrils may possibly assist effective proton conduction channels by the Grotthuss mechanism. 38 Therefore, we synthesized a control peptide molecule ( Fig.…”
Section: Electrical Measurements Of Btbt-peptide and C8-btbtpeptide Fmentioning
confidence: 99%